Tolerance and its relationship to the quality of married life among married couples (Journal of Human Sciences, 2023)
This study aims to identify the relationship between tolerance and the quality of marital life among a sample of faculty members at the Faculty of Arts at Sebha University, and it relied on the descriptive analytical approach. The study sample consisted of (38) male and female professors who were married, they were chosen randomly, and after verifying the validity and reliability of the study tools, the study questions were answered.-There is a statistically significant relationship between tolerance and quality of life among the study sample-There are statistically significant differences in tolerance due to the gender variable-There are no statistically significant differences in the quality of life due to the gender variable-There are no statistically significant differences in tolerance due to the educational qualification variable-There are statistically significant differences in the quality of life due to the educational qualification variable- There are no statistically significant differences in tolerance and quality of life due to the age variable- There are no statistically significant differences in tolerance and quality of life due to the variable duration of marriage.